Social Construction of Academic Staff in Order to Create Professional Tutors - Prasetya, Agus; Muwarni, Juli; Purwantiningsih, Ary (OJS Universitas Muhammadiyah Gresik, 2024)
The Universitas Terbuka (UT) is the 45th State University in Indonesia which was inaugurated based on Presidential Decree No. 41 of 1984, with the Distance Learning System (SBJJ) model. The background of this research is the existence of a Research Gap, namely Tutor behavior in academic and administrative matters, such as for example Tutors are late in reporting tuweb result files, wrong assessment formats, limited IT mastery, this can cause disruption of tutorials. The purpose of this research is that lecturers who provide tutorials at UT, are professional academically and administratively. The problems that occur, many tutors at UT are only part-time, tutors often take permission, come late, collect files late, limited IT skills. This research is a qualitative research with descriptions in the form of narratives, stories, words on the subjects studied. While the novelty of this research is the understanding of assessment procedures and limited IT tutors, which is the cause of tutor problems. Data collection methods through observation, in-depth interviews, and documentation, data sources are obtained from primary data, namely tutors, while secondary sources are managers. Data analysis using the Miles and Huberman Interactive model which includes the stages of Data Collection, Data Reduction, Data Display, and Data Conclution and Data validity through triangulation both methods, sources, time. To explore the data, researchers used the study of L.Berger, T.Luckman's Social Construction Action theory, which is a theory that focuses on human social action in their social interactions in society. The results showed that the tutor construction process required academic and administrative social changes in tutors, to create a culture of quality, improve the quality of IT tutors.